Evaluation of current Australian health service accreditation processes (ACCREDIT-CAP): protocol for a mixed-method research project. Issue 4 (4th August 2012) - Hinchcliff, Reece; Greenfield, David; Moldovan, Max; Pawsey, Marjorie; Mumford, Virginia; Westbrook, Johanna Irene; Braithwaite, Jeffrey
Abstract : Introduction: Accreditation programmes aim to improve the quality and safety of health services, and have been widely implemented. However, there is conflicting evidence regarding the outcomes of existing programmes. The Accreditation Collaborative for the Conduct of Research, Evaluation and Designated Investigations through Teamwork-Current Accreditation Processes (ACCREDIT-CAP) project is designed to address key gaps in the literature by evaluating the current processes of three accreditation programmes used across Australian acute, primary and aged care services. Methods and design: The project comprises three mixed-method studies involving documentary analyses, surveys, focus groups and individual interviews. Study samples will comprise stakeholders from across the Australian healthcare system: accreditation agencies; federal and state government departments; consumer advocates; professional colleges and associations; and staff of acute, primary and aged care services. Sample sizes have been determined to ensure results allow robust conclusions. Qualitative information will be thematically analysed, supported by the use of textual grouping software. Quantitative data will be subjected to a variety of analytical procedures, including descriptive and comparative statistics. The results are designed to inform health system policy and planning decisions in Australia and internationally. Ethics and dissemination: The project has been approved by the University of New South Wales Human Research Ethics Committee (approval number HREC 10274). Results will be reported to partner organisations, healthcare consumers and other stakeholders via peer-reviewed publications, conference and seminar presentations, and a publicly accessible website.